INFERIORITY FEELING OF OLIVER TWIST IN ROMAN POLANSKI'S OLIVER TWIST: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - Akhtaj, Nur Aini (2010)
This research paper investigates how inferiority feeling of Oliver Twist as the major character is reflected in Roman Polanski's Oliver Twist. Therefore, the study analyzes the movie in terms of its structural elements and based on the individual psychological analysis. The writer uses qualitative study, in which the primary data is the movie of Oliver Twist, and secondary data is the other data related to the research such as some books of individual psychological theory by Alfred Adler, movie script, commentaries, internet, and other relevant information. The method of data collection is library research. The technique of data analysis is descriptive analysis. The result of the analysis is as follows. Firstly, the structural element of the movie presents a solid unity. Secondly, the individual psychological analysis shows that the inferiority feeling of Oliver Twist influences his personality in facing social life. He feels there is no one who loves and cares him because he is an orphan and poor boy. Those problems produce weak feeling that affects his personality. His weakness in social sphere drives him to overcome his inferiority. He compensates his weaknesses by striving to get his goal of life. Finally, he can live happily and peacefully with the new family